An Optimalization of Merdeka Curriculum through Developing an E-assessment in SMAN 1 Payakumbuh - Sundari, Putri Dwi; Sari, Silvi Yulia; Aulia, Fauzan; Hidayati, Hidayati (Fakultas MIPA Universitas Negeri Padang, 2024)
This Community Partnership Program (PKM) activity aims to provide understanding and skills to teachers at SMA Negeri 1 Payakumbuh in the context of implementing the Merdeka curriculum. A total of 18 teachers participated as participants in this activity, representing the fields of study at the school. There are three stages that PKM participants go through during the implementation of activities, namely the stage of strengthening understanding of the independent curriculum, evaluating learning and making e-assessments, the demonstration stage and independent work. Based on the PKM activities carried out, it can be seen that the participant response was positive and the participants' understanding of the material presented during the activity was very good with an average score of 3.46 out of a maximum score of 4.00.